Cultural contingencies and ideological practices in the postmodern intellectual: an interpretive essay (Revista revoluciones, 2025)
This essay discusses the relevance of employing behavioral analysis categories developed in recent years to examine cultural phenomena. The chosen object of interpretive analysis is the behavior of the postmodern intellectual. To this end, the definitions of categories under the heading of cultural contingencies (interlocking contingencies, metacontingencies, culturants, macrocontingencies, and cultural cusps) are first reviewed, followed by an appraisal of the modern and postmodern contexts regarding their types of intellectuality. As an illustration, a specific development of postmodern thought—queer ideology—is selected to be subjected to cultural behavioral analysis based on the proposed categories. It is concluded that these categories make it possible to characterize the main guidelines of any socio-behavioral episode, as they specify the antecedents (discriminative stimuli) and consequences that situate it concretely. In the analyzed case, discourses that delegitimize modernity as an authentic discourse and establish criticism and self-criticism as defining factors of any thought process provide the discriminative stimuli for the emergence of postmodern theses, which are then consolidated by their reception among consumers.
Keywords: contingency; culture; ideology; intellectuality; postmodernity